2019
DOI: 10.3171/2018.10.spine181094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sagittal spinopelvic alignment on clinical outcomes and health-related quality of life after decompression surgery without fusion for lumbar spinal stenosis

Abstract: OBJECTIVEPatients with lumbar spinal stenosis (LSS) tend to bend forward to relieve neurological symptoms. They therefore have a positive sagittal vertical axis (SVA). The importance of the SVA value is well known in the field of adult spinal deformity; however, little is known about its impact on LSS. The authors sought to investigate the impact of sagittal spinopelvic alignment on clinical outcome and health-related quality of life (HRQOL) after decompression surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 13 publications
1
40
1
Order By: Relevance
“…Previous studies regarding sagittal balance have demonstrated that lumbar malalignment after spine surgery may cause poor clinical outcomes [15,16]. patients should be provided proper correction of the spinal alignment in order to prevent complications to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding sagittal balance have demonstrated that lumbar malalignment after spine surgery may cause poor clinical outcomes [15,16]. patients should be provided proper correction of the spinal alignment in order to prevent complications to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the spinal sagittal stability after vertebral surgery has been shown in many studies. 7,27,31,32 The spinal sagittal parameters include SVA, LL, and TL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported sagittal spinal misalignment has been shown to be a risk factor for LBP after fusion. [16][17][18] However, to our knowledge, there is no study regarding on the impact factors of LBP after OLIF. It was our hypothesis that the restored the sagittal spinopelvic alignment is beneficial to relieve the LBP.…”
Section: Introductionmentioning
confidence: 99%